2011
DOI: 10.1590/s0102-86502011000700016
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative glutamine infusion improves glycemia in heart surgery patients

Abstract: PURPOSE:To evaluate the effects of pre-operative L-alanyl-glutamine (L-Ala-Gln) on blood glucose control in patients with coronary obstruction, selected for myocardial revascularization. METHODS: Twenty-two patients (63±8 years) were randomly assigned to receive 250ml of L-Ala-Gln 20% plus saline 750 ml (Group L-Ala-Gln, n=11) or saline 1000 ml (Group Saline, n=11) over 3 hours before operation. Pre-operative blood samples were collected 3h before (T-1) and at the beginning of the surgical procedure (T-2). Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Acute oral administration of Gln improves glucose tolerance in subjects with or without diabetes, while chronic dietary supplementation of Gln for 6 weeks reduces systolic blood pressure, fasting blood glucose, and improves body composition in patients with type 2 diabetes [28,29]. In addition, Gln administration decreases glycemia in adolescents with type 1 diabetes and in patients undergoing myocardial revascularization [30,31]. Parenteral administration of Gln also prevents the decrease in insulin sensitivity in multiple-trauma patients [32].…”
Section: L-glutamine and Cardiometabolic Diseasementioning
confidence: 99%
“…Acute oral administration of Gln improves glucose tolerance in subjects with or without diabetes, while chronic dietary supplementation of Gln for 6 weeks reduces systolic blood pressure, fasting blood glucose, and improves body composition in patients with type 2 diabetes [28,29]. In addition, Gln administration decreases glycemia in adolescents with type 1 diabetes and in patients undergoing myocardial revascularization [30,31]. Parenteral administration of Gln also prevents the decrease in insulin sensitivity in multiple-trauma patients [32].…”
Section: L-glutamine and Cardiometabolic Diseasementioning
confidence: 99%
“…35,36 Inclusion of aspartate, glutamate and glutamine in animal heart perfusates and cardioplegic solutions improves metabolic and functional recovery and elevates high-energy phosphate levels postischemia, and they have been used experimentally in cardioplegic solutions with good results. 17,18,27,40 Questions regarding the efficacy of these amino acids may arise from xenotypic differences, protocol incompatibility or the use of free acids versus amino acid salts. 35 Another assumption is that perfused amino acids are readily available for intracellular functions, without regard to transporter activity.…”
Section: Tryptophanmentioning
confidence: 99%
“…Previous experimental studies have demonstrated that GLN had favorable effects against IR injury. The studies found that pretreatment with GLN reduced oxidative stress and enhanced cell survival locally 16 18 and had a protective effect against organ injury following IR 19 , 20 . However, these studies provided GLN before tissue ischemia.…”
Section: Introductionmentioning
confidence: 99%